Presentation of Traditional Folktale Through 3-Dimensional Animation Film in Gromore Studio YouTube Channel, A Study Case - Hutomo Setia Budi; I Wayan Adnyana; I Wayan Swandi; I Nyoman Suardina (Jurnal Desain Komunikasi Visual Nirmana, 2024)
This research aimed to discover audience responses toward animation content that tells about folklore and is uploaded onto the Gromore Studio YouTube platform. It is designed based on interview data as well as observation of the view count, comments, and literature study. This research included cultural studies which studied social culture phenomena by using descriptive quantitative analysis methods with emphasis on discovering the comparison of positive and negative comments, and the comparison between like and dislike counts from the folklore video which was uploaded by Gromore Studio. The results of this research showed that the presentation of legendary folktales received outstanding responses from the audience with Indonesians as the majority. Comments given by the audience mostly showed positive feedback and support toward animation content produced by Gromore Studio which lifted the local cultures and stories, packed into interesting visual media. Through the positive responses in the comments, it can be concluded that the animations by Gromore Studio in traditional folktales became very welcomed by Indonesian audiences.